Pengaruh Struktur Kepemilikan Terhadap Price to Book Value dengan Manajemen Laba sebagai Variabel Intervening - Dewanti, Kartika Widya Tri; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi, 2018)
The purpose of this research is to examine the impact of ownership structure consisting of institutional and managerial ownership to price to book value ratio (PBV) with earnings management as intervening variable. The samples of this research are 34 manufacturing companies that have been selected using purposive sampling method from their population of 139 companies listed in Indonesia Stock Exchange (IDX) during 2014-2016 period consecutively. Descriptive statistical analysis, classical assumption test and path analysis is analyticals technique used in this research. The examination of this research shows that the result of institutional and managerial ownership negatively affect on PBV, institutional and managerial ownership have no impact on earnings management, earnings management have positive effect on PBV, earnings management is not an intervening variable in the impact of institutional and managerial ownership on PBV.